DESIGN OF ERGONOMIC WEED-WEEDING MACHINE WITH ANTHROPOMETRIC APPROACH - Subchan Asyari; Sugiono; Panji Deoranto; Bambang Dwi Argo (Jurnal Teknologi Pertanian, 2025)
In the weeding process, farmers still use the conventional method of swinging the sickle horizontally over the weed-covered soil repeatedly until the weed stems are cut and flush with the ground. This process can lead to rapid fatigue, especially in the musculoskeletal system or skeletal muscles. When weeding, the average farmer's back bends at a 90-degree angle while repeatedly pulling out weeds. In designing this machine, an anthropometric approach is used to determine the ergonomic design of the weed mower that provides worker comfort. Anthropometry is the study of human body dimensions and their application in design, including physical geometry, mass, strength, and body characteristics such as shape and size. Humans vary in shape, size, height, and weight. The sample size is 23 workers. Based on the research conducted on the weed, the researchers proposed an ergonomic weed-weeding machine design based on an anthropometric approach. The anthropometric measurements obtained are the height of the weed-weeding machine is 120.7 cm, the width range of the weed-weeding machine is 46.8 cm, and the depth range of the weed-weeding machine is 42.0 cm, using the results of the 50th percentile. The design of this weed-weeding machine is expected to have practical implications, including increased comfort and work efficiency for farmers, which in turn can speed up the weeding process and increase rice productivity. This design is also expected to encourage innovation in the field of work system design and ergonomics.